PENERAPAN TEKNIK MEMBACA SEKILAS UNTUK MENENTUKAN GAGASAN POKOK SISWA KELAS IV SDN 015 PAGARAN TAPAH DARUSSALAM - Mariyana ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the idea of the low ability determining principal grade IV SDN015 Pagaran Tapah Darussalam. Goals to be achieved in this research is to determine ideagrade IV principal of SDN 015 Pagaran Tapah Darussalam through the application of thetechniques implemented for 1 month. This research was conducted in SDN 015 PagaranTapah Darussalam. Classes are meticulous researchers are class IV by the number ofstudents as many as 24 people. This classroom action research was started in early August2016. This form of research is classroom action research. The research instrument consists ofinstruments teacher and student activity sheets and achievement test. Based on the research,the conclusion to this research the skills of students in the ability to determine the main ideahas increased. On preliminary data low category with a percentage of 54.2% while in sikus Ifirst encounter increased to 65.1% low category, at a second meeting to 68.8% and thesecond cycle increased to 81.3% categorized as moderate and kemablai increased in thesecond meeting be 85.7% higher category